Toward optimal clearance: A universal affinity‐based mass spectrometry approach for comprehensive ELISA reagent coverage evaluation and HCP hitchhiker analysis. (11th March 2022) - Seisenberger, Christina; Graf, Tobias; Haindl, Markus; Wegele, Harald; Wiedmann, Michael; Wohlrab, Stefanie
Abstract: In the control strategy for process related impurities in biopharmaceuticals, the enzyme linked immunosorbent assay (ELISA) is the method of choice for the quantification of host cell proteins (HCPs). Besides two dimensional‐western blots (2D‐WB), the coverage of ELISA antibodies is increasingly evaluated by affinity purification‐based liquid chromatography–tandem mass spectrometry (AP‐MS) methods. However, all these methods face the problem of unspecific binding issues between antibodies and the matrix, involving the application of arbitrarily defined thresholds during data evaluation. To solve this, a new approach (optimized AP‐MS) was developed in this study, for which a cleavable linker was conjugated to the ELISA antibodies enabling the subsequent isolation of specifically interacting HCPs. By comparing both approaches in terms of method variability and the number of false positive or negative hits, we could demonstrate that the optimized AP‐MS method is very reproducible and superior in the identification of antibody detection gaps, while previously described strategies suffered from over‐ or underestimating the coverage. As only antibody associated HCPs were identified, we demonstrated that the method is beneficial for hitchhiker analysis. Overall, the method described herein has proven as a powerful tool for reliable coverage determination of ELISA antibodies, without the need to arbitrarily exclude HCPs during the coverage evaluation.